2005
DOI: 10.1007/s10865-005-3666-1
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Construct Validity of the Pain Distress Inventory

Abstract: We conducted three studies to evaluate further the reliability and construct validity of a new self-report instrument, the Pain Distress Inventory (PDI; Osman et al., 2003, The Pain Distress Inventory: Development and initial psychometric properties, J. Clin. Psychol. 59: 767-785). In Study I, exploratory and confirmatory factor analytic results confirmed the replicability of the four-factor oblique solution of the PDI in a mixed sample of students and nonstudents. We also found strong evidence for criterion-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 22 publications
0
61
0
1
Order By: Relevance
“…Granot and colleagues 31 studied gender differences in chest pain perception and reported that women scored the intensity of their chest pain significantly higher than men. Gender differences in chronic pain and in pain distress measures have also been reported, 32,33 and both physiologic and psychological mechanisms for gender differences related to pain have been posed. The trend toward gender differences in postoperative pain reported by the ICD patients in this study mirror findings from other studies reporting the general differences in the way that men and women experience pain.…”
Section: Discussionmentioning
confidence: 99%
“…Granot and colleagues 31 studied gender differences in chest pain perception and reported that women scored the intensity of their chest pain significantly higher than men. Gender differences in chronic pain and in pain distress measures have also been reported, 32,33 and both physiologic and psychological mechanisms for gender differences related to pain have been posed. The trend toward gender differences in postoperative pain reported by the ICD patients in this study mirror findings from other studies reporting the general differences in the way that men and women experience pain.…”
Section: Discussionmentioning
confidence: 99%
“…Physical pain distress was assessed by administration of the 26-item Pain Distress Inventory (PDI; Osman et al, 2003), with the pain sensitivity subscale being used to assess self-perceived sensitivity to physical pain. While never before used in a study of self-harm, it has been used in community samples (Osman et al, 2005). Overall internal consistency for this sample was very good, α = .95, as was the case for the sensitivity subscale: α =94.…”
Section: Methodsmentioning
confidence: 80%
“…PDI scores have predicted pain symptoms and have differentiated between clinic and nonclinic samples receiving treatment for medical or pain-related experiences (Osman, et al, 2003). The factorial structure of the PDI has been replicated in students and nonstudents and among African American and Caucasian young adults (Osman et al, 2005). Results of a second-order confirmatory factor analysis supported the construct validity of the total PDI score (Robust χ 2 = 74.18, Comparative Fit Index = .98).…”
Section: Instrumentsmentioning
confidence: 78%
“…Results of a second-order confirmatory factor analysis supported the construct validity of the total PDI score (Robust χ 2 = 74.18, Comparative Fit Index = .98). Total PDI score evinced moderate correlations (.45 to .72) with other pain-related measures and a coefficient alpha of .93 and .94 in two studies (Osman et al, 2005). Coefficient alpha among African American undergraduate and graduate students was .94 (Osman et al, 2005).…”
Section: Instrumentsmentioning
confidence: 87%
See 1 more Smart Citation